Understanding families : a global introduction - McKie, Linda; Callan, Samantha (SAGE, 2012)
"Families are at the core of our society. Our experience of them affects many aspects of our everyday lives shaping our expectations and future plans. Written by field experts this clear, engaging book adopts a global perspective to usefully examine how modern families can be explored and understood. Packed with critical pedagogy, including case-studies, think points, key words and a glossary, it guides students through topics such as relationships, sexualities and paid and unpaid work. The book also: Applies key social theories from classical sociological theory and contemporary analysis; Examines best practice for researching families and family life; Explores the role of government policies and practices; This comprehensive introduction to the study of families and relationships is a timely resource for students and lecturers working across the social sciences."--Publisher's website